Derivative parameters of electroencephalograms and their measurement methods - Misiukas Misiūnas, Andrius Vytautas; Meškauskas, Tadas; Samaitienė, Rūta (Lietuvos matematikos rinkinys, 2016)
The derivative parameters of electroencephalogram (EEG): baseline, upslope, downslope and width of EEG spikes are analysed in this work. Automatic methods of their measurement are presented. Validation of discussed parameters against their possible range (provided by neurologists) lets us to exclude some falsely positively detected spikes thus improving accuracy of the spike detection algorithm. These parameters might have some correlation between them and diagnosis of the  atients.
Keywords: EEG processing; epilepsy; EEG spikes; epileptiform discharges